Dynamics of invasion and dissemination of H5N6 highly pathogenic avian influenza viruses in 2016–2017 winter in Japan - ITO, Toshihiro; OZAKI, Hiroichi; MATSUNO, Keita; OKAMATSU, Masatoshi; SODA, Kosuke; SAKODA, Yoshihiro; YAMAGUCHI, Tsuyoshi; USUI, Tatsufumi; ITO, Hiroshi (Journal of Veterinary Medical Science, 2021)
Large highly pathogenic avian influenza (HPAI) outbreaks caused by clade 2.3.4.4e H5N6 viruses occurred in Japan during the 2016–2017 winter. To date, several reports regarding these outbreaks have been published, however a comprehensive study including geographical and time course validations has not been performed. Herein, 58 Japanese HPAI virus (HPAIV) isolates from the 2016–2017 season were added for phylogenetic analyses and the antigenic relationships among the causal viruses were elucidated. The locations where HPAIVs were found in the early phase of the outbreaks were clustered into three regions. Genotypes C1, C5, and C6–8 HPAIVs were found in specific areas. Two strains had phylogenetically distinct hemagglutinin (HA) and non-structural (NS) genes from other previously identified strains, respectively. The estimated latest divergence date between the viral genotypes suggests that genetic reassortment occurred in bird populations before their winter migration to Japan. Antigenic differences in 2016–2017 HPAIVs were not observed, suggesting that antibody pressure in the birds did not contribute to the selection of HPAIV genotypes. In the late phase, the majority of HPAI cases in wild birds occurred south of the lake freezing line. At the end of the outbreak, HPAI re-occurred in East coast region, which may be due to the spring migration route of Anas bird species. These trends were similar to those observed in the 2010–2011 outbreaks, suggesting there is a typical pattern of seeding and dissemination of HPAIV in Japan.